2009 30th IEEE Symposium on Security and Privacy 2009
DOI: 10.1109/sp.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

It's No Secret. Measuring the Security and Reliability of Authentication via “Secret” Questions

Abstract: All four of the most popular webmail providers -AOL, Google, Microsoft, and Yahoo! -rely on personal questions as the secondary authentication secrets used to reset account passwords. The security of these questions has received limited formal scrutiny, almost all of which predates webmail. We ran a user study to measure the reliability and security of the questions used by all four webmail providers. We asked participants to answer these questions and then asked their acquaintances to guess their answers. Acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 8 publications
2
112
2
Order By: Relevance
“…Challenge question authentication is a knowledge-based feature, which is widely seen as a credential recovery technique (Just and Aspinall 2009a;Schechter et al 2009). This method has been used as a second factor feature and employed for customer verification in online and telephone banking (Rabkin 2008;Just and Aspinall 2012).…”
Section: Challenge Question Authenticationmentioning
confidence: 99%
See 4 more Smart Citations
“…Challenge question authentication is a knowledge-based feature, which is widely seen as a credential recovery technique (Just and Aspinall 2009a;Schechter et al 2009). This method has been used as a second factor feature and employed for customer verification in online and telephone banking (Rabkin 2008;Just and Aspinall 2012).…”
Section: Challenge Question Authenticationmentioning
confidence: 99%
“…Security findings of their study indicate low security level for 5 of their 60 questions. Schechter et al (2009) Renaud and Just (2010) proposed associative picture based cues with multiple choice answers, which achieved a 13% increase in the memorability with 77% correct answers. However, the security analysis revealed that 38% of the times, answers were guessed by close friends.…”
Section: Challenge Question Authenticationmentioning
confidence: 99%
See 3 more Smart Citations